2010
DOI: 10.1021/la903637t
|View full text |Cite
|
Sign up to set email alerts
|

SERS Study of Rotational Isomerization of Cysteamine Induced by Magnetic Pulling Force

Abstract: The effects of unidirectional pulling forces on covalently bridged cysteamine between superparamagnetic particles and Ag nanoparticles (NPs) were studied with SERS spectroscopy. With an increase in the pulling force from 0 to 100 pN per magnetic particle, the nu(C-S)(Trans)/nu(C-S)(Gauche) intensity ratio was increased from 0.6 to 1.08, the Raman frequency of nu(C-S)(Trans) was shifted from 716 to 719 cm(-1), and the Raman bands associated with the amide groups were diminished. From these observations, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…1A illustrates a typical Cys SERS spectrum in the range of 500-1250 cm À1 collected in DI water, showing the characteristic SERS bands of Cys. A very strong Raman band appears at $635 cm À1 , which can be assigned to the C-S stretching vibration mode of a gauche-conformation of the Cys molecule; while a weak band observed at $715 cm À1 can be assigned to the trans-conformation [34,[38][39][40][41][42]. This indicates that both conformers coexist in the Cys SAM on the substrate, and the gauche one predominates.…”
Section: Formation Of Cys Sam and Background Spectrum Of The Substratementioning
confidence: 94%
“…1A illustrates a typical Cys SERS spectrum in the range of 500-1250 cm À1 collected in DI water, showing the characteristic SERS bands of Cys. A very strong Raman band appears at $635 cm À1 , which can be assigned to the C-S stretching vibration mode of a gauche-conformation of the Cys molecule; while a weak band observed at $715 cm À1 can be assigned to the trans-conformation [34,[38][39][40][41][42]. This indicates that both conformers coexist in the Cys SAM on the substrate, and the gauche one predominates.…”
Section: Formation Of Cys Sam and Background Spectrum Of The Substratementioning
confidence: 94%
“…With an increase in the pulling force from 0 to 100 pN per magnetic bead, the surface-enhanced Raman scattering (SERS) intensity ratio of ν (C–S) trans / ν (C–S) gauche , corresponding to the equilibrium isomer ratio of cysteamine, increased from 0.6 to 1.08, indicating an increase in the trans form from 37% to 52%. 102 This result suggested that the trans form, which has a longer molecular structure than the gauche form, is stabilized under the pulled condition. A quartz crystal microbalance (QCM) is known as an extremely sensitive device for the measurement of very small weight changes in the order of ng.…”
Section: Application Of Magnetic Field-gradient Forcementioning
confidence: 99%
“…It can be concluded from the present study that the electromagnetophoretic force can be used to shift the chemical equilibrium of cysteamine, which was previously observed by applying a magnetophoretic pulling force through the magnetic beads to cysteamine molecules. 11 It can be said for the advantage of an electromagnetophoretic force over a magnetophoretic force that the force can be applied to any types of particles in conductive solutions. Further application of an electromagnetophoretic force to various molecules, especially biomolecules, is desired to develop its potential as a novel characterization method in the study of mechanobiochemistry.…”
Section: Measurement Of Sers Spectramentioning
confidence: 99%